High entropy lithium-rich manganese-based porous oxide nanofibers and preparation method and application thereof

High-entropy lithium-rich manganese-based layered oxide porous nanofibers were prepared through high-voltage electrospinning, which solved the capacity fading and cycle stability problems of existing lithium-rich manganese-based cathode materials, achieved low voltage drop and high structural stability, and improved Lithium-ion battery performance.

CN118326565BActive Publication Date: 2025-01-21深圳市速方新能源科技有限公司

Patent Information

Application Number
CN202410502077.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-01-21
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have problems such as fast capacity decay, oxygen release, low first charge and discharge efficiency, poor cycle stability and obvious voltage decay, which hinders its commercial application.

Method used

High-entropy lithium-rich manganese-based layered oxide porous nanofibers were prepared using a high-pressure electrospinning method. By building high-level internal configuration entropy, the electronic structure of Mn-O was optimized to avoid transition metal ion migration.

Benefits of technology

It achieves low voltage drop, high structural stability and resistance to electrolyte corrosion, improves the cycle stability and rate performance of lithium-ion batteries, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118326565B_ABST
    Figure CN118326565B_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy lithium-rich manganese-based layered oxide porous nanofiber and a preparation method and application thereof. The chemical formula of the high-entropy lithium-rich manganese-based layered oxide porous nanofiber is Li{Li 0.2 Mn a Ni b Co c Al d TM 0.8‑a‑b‑c‑d}O2; its preparation method is as follows: S1, dissolving polyacrylonitrile and polymethyl methacrylate in dimethylformamide to obtain a polymer solution; S2, dissolving lithium salt, manganese salt, nickel salt, cobalt salt, aluminum salt and TM salt in dimethylformamide to obtain a mixed metal salt solution; S3, adding the mixed metal salt solution to the polymer solution to obtain an intermediate mixed solution; S4, using the intermediate mixed solution to obtain a precursor nanofiber by a high-voltage electrostatic spinning method; S5, calcining the precursor nanofiber, and cooling to obtain a high-entropy lithium-rich manganese-based layered oxide porous nanofiber. The high-entropy lithium-rich manganese-based layered oxide porous nanofiber is used to prepare a positive electrode material for lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a high-entropy lithium-rich manganese-based layered oxide porous nanofiber and a preparation method and application thereof. Background Art

[0002] Lithium-rich manganese-based cathode materials have the advantages of high specific capacity (above 250mAh / g), high safety and low cost, and have become the next generation of new lithium-ion battery cathode materials with great development potential. However, lithium-rich manganese-based cathode materials have problems such as fast capacity decay, oxygen release, very low initial charge and discharge efficiency, poor cycle stability and obvious voltage decay, which hinder the commercial application of lithium-rich manganese-based cathode materials. At present, the synthesis methods of lithium-rich manganese-based cathode materials mainly include liquid phase method and solid phase method. The liquid phase method is usually a co-precipitation method and a sol-gel method. Such methods are relatively complex and require strict control of reaction conditions and post-processing process flow, and the preparation cycle is too long; the solid phase method generally includes a molten salt method and a ball milling method, and there is uneven mixing of material precursors, and impurities are easily introduced during the preparation process, affecting the production quality; therefore, finding a lithium-rich manganese-based cathode material with simple process, low environmental requirements, good reproducibility, and suitable for mass production has become one of the focuses of lithium-ion battery research. Summary of the invention

[0003] The purpose of the present invention is to provide a high-entropy lithium-rich manganese-based porous oxide nanofiber with simple process, low environmental requirements, good reproducibility and suitable for mass production, as well as a preparation method and application thereof in view of the above problems.

[0004] In order to achieve the above object, the technical solution of the present invention is:

[0005] A high entropy lithium-rich manganese-based layered oxide porous nanofiber, wherein the chemical formula of the high entropy lithium-rich manganese-based layered oxide porous nanofiber is Li{Li 0.2 Mn a Ni b Co c Al d TM 0.8-a-b-c-d}O2, wherein 0.4≤a≤0.5, 0.1≤b≤0.2, 0.1≤c≤0.2, 0.01≤d≤0.05; the TM metal element includes one of Ti, V, Cr, Zr, Mo, W, Nb, Ru, Sn, Ce, and La.

[0006] A method for preparing high-entropy lithium-rich manganese-based porous oxide nanofibers comprises the following steps:

[0007] S1, dissolving polyacrylonitrile and polymethyl methacrylate in dimethylformamide to obtain a high molecular polymer solution;

[0008] S2, dissolving lithium salt, manganese salt, nickel salt, cobalt salt, aluminum salt and TM salt in dimethylformamide according to a molar ratio to obtain a mixed metal salt solution;

[0009] S3, adding the mixed metal salt solution to the high molecular polymer solution and mixing evenly to obtain an intermediate mixed solution;

[0010] S4, transferring the intermediate mixed solution into a syringe, and preparing precursor nanofibers by high-voltage electrospinning;

[0011] S5, drying the precursor nanofibers and then calcining them in stages, and obtaining the high-entropy lithium-rich manganese-based porous oxide nanofibers after cooling.

[0012] Furthermore, in step S2, the lithium salt is a mixture of one or more of lithium carbonate, lithium hydroxide, lithium chloride, and lithium acetate; the manganese salt is a mixture of one or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate; the nickel salt is a mixture of one or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate; the cobalt salt is a mixture of one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate; the aluminum salt is a mixture of one or more of aluminum sulfate, aluminum nitrate, and aluminum chloride; and the TM salt is a mixture of one or more of hydrochloride, sulfate, and nitrate.

[0013] Furthermore, in the mixed metal salt solution of step S2, the ratio of the amount of lithium ion, manganese ion, nickel ion, cobalt ion and aluminum ion is 1.2:0.4-0.5:0.1-0.2:0.1-0.2:0.01-0.05.

[0014] Furthermore, during the high-voltage electrospinning process of step S4, the electrospinning voltage is 10-20 kV, the temperature is 25-40° C., the syringe feed rate is 0.001-0.02 mm / s, and the distance between the receiver and the syringe is 15-20 cm.

[0015] Furthermore, the step S5 specifically includes the following steps:

[0016] S51, heating the dried precursor nanofibers to 200-300° C. at room temperature at a heating rate of 1° C. / min and keeping the temperature for 1.5-2.5 h;

[0017] S52, heating to 450-550°C at a heating rate of 1.5-4.5°C / min and keeping warm for 3-6h;

[0018] S53, heating to 800-900°C at a heating rate of 1.5-4.5°C / min and calcining at a constant temperature for 10-18h; after cooling to room temperature, the high entropy lithium-rich manganese-based layered oxide porous nanofibers are obtained.

[0019] The invention discloses an application of high-entropy lithium-rich manganese-based layered oxide porous nanofibers. The high-entropy lithium-rich manganese-based layered oxide porous nanofibers are used to prepare lithium-ion battery positive electrode materials. The lithium-ion battery prepared by using the lithium-ion battery positive electrode material has a cycle voltage drop of 0.9 mV / cycle in the first 200 cycles and a 1C capacity of 282 mAh / g.

[0020] Compared with the prior art, the present invention has the following advantages and positive effects:

[0021] 1. The low voltage drop high entropy lithium-rich manganese-based layered oxide porous nanofibers of the present invention optimize the electronic structure of Mn-O by constructing a higher intralayer configuration entropy, effectively avoiding the migration of transition metal ions, thereby greatly improving the structural stability and electrolyte corrosion resistance of the lithium-rich layered positive electrode, and achieving stable capacity and voltage;

[0022] 2. The preparation method of the low voltage drop high entropy lithium-rich manganese-based porous nanofibers of the present invention is simple and easy, and the morphology is controllable. The battery prepared from the material has excellent discharge performance, rate performance and cycle stability; the preparation method uses electrospinning to control the one-dimensional morphology structure, which is conducive to accelerating the transmission of lithium ions and the transfer of electrons, and improving the rate performance of lithium-ion batteries;

[0023] 3. The lithium-ion battery prepared by the low voltage drop high entropy lithium-manganese-based layered oxide porous nanofibers of the present invention has a capacity retention rate of up to 98% after 200 cycles, and a voltage decay rate of only 0.9 mV / cycle. It has electrochemical properties that are superior to most lithium-rich manganese-based positive electrode materials, and improves the performance and effect of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 This is the SEM electron microscope image of high entropy lithium-rich manganese-based layered oxide porous nanofibers;

[0026] Figure 2 This is a cyclic stability curve of high entropy lithium-rich manganese-based porous oxide nanofibers;

[0027] Figure 3 This is the voltage drop attenuation curve of high entropy lithium-rich manganese-based layered oxide porous nanofibers. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.

[0029] Example 1

[0030] This embodiment discloses a low voltage drop high entropy lithium-rich manganese-based porous oxide nanofiber, the chemical formula of which is Li{Li 0.2 Mn 0.45 Ni 0.15 Co 0.1 Al 0.05 Cr 0.05}O2.

[0031] The preparation steps and operating parameters of the above-mentioned low voltage drop high entropy lithium-rich manganese-based porous nanofibers are as follows:

[0032] 1. Dissolve polyacrylonitrile and polymethyl methacrylate in dimethylformamide at a mass ratio of 3:1 and a total mass of 5 g to obtain a polymer solution;

[0033] 2. Dissolve Li, Mn, Ni, Co, Al, and Cr in dimethylformamide at a molar ratio of 1.2:0.45:0.15:0.1:0.05:0.05 to obtain a mixed metal salt solution;

[0034] 3. Mix the mixed metal salt solution and the high molecular polymer solution and stir continuously for 2 to 10 hours to obtain an intermediate mixed solution;

[0035] 4. The obtained intermediate mixed solution was transferred into a syringe, and electrospinning was performed by electrospinning at a receiving distance of 12 cm, a flow rate of 1.0 mL / h adjusted by a syringe pump, and a voltage of 18 kV to obtain non-woven polyacrylonitrile polymethyl methacrylate composite nanofibers;

[0036] 5. After spinning, the polyacrylonitrile polymethyl methacrylate composite nanofibers are placed in a muffle furnace, heated to 200°C at a heating rate of 1°C / min and calcined for 2h for material aging treatment, then heated to 500°C at a heating rate of 3°C / min and calcined for 4h, and then heated to 850°C at a heating rate of 3°C / min for carbonization for 12h. After cooling, low voltage drop and high entropy lithium-rich manganese-based porous oxide nanofibers Li{Li 0.2 Mn 0.45 Ni 0.15 Co0.1 Al 0.05 Cr 0.05}O2.

[0037] The prepared low voltage drop high entropy lithium-rich manganese-based porous nanofibers can be used to prepare positive electrode materials for lithium-ion batteries.

[0038] Example 2

[0039] This embodiment discloses a low voltage drop high entropy lithium-rich manganese-based porous oxide nanofiber, the chemical formula of which is Li{Li 0.2 Mn 0.5 Ni 0.1 Co 0.1 Al 0.06 Cr 0.04}O2.

[0040] The preparation steps and operating parameters of the above-mentioned low voltage drop high entropy lithium-rich manganese-based porous nanofibers are as follows:

[0041] 1. Dissolve polyacrylonitrile and polymethyl methacrylate in dimethylformamide at a mass ratio of 3:1 and a total mass of 5 g to obtain a polymer solution;

[0042] 2. Dissolve Li, Mn, Ni, Co, Al, and Cr in dimethylformamide at a molar ratio of 1.2:0.5:0.1:0.1:0.06:0.04 to obtain a mixed metal salt solution;

[0043] 3. Mix the mixed metal salt solution and the high molecular polymer solution and stir continuously for 2 to 10 hours to obtain an intermediate mixed solution;

[0044] 4. The obtained intermediate mixed solution was transferred into a syringe, and electrospinning was performed by electrospinning at a receiving distance of 12 cm, a flow rate of 1.0 mL / h adjusted by a syringe pump, and a voltage of 18 kV to obtain non-woven polyacrylonitrile polymethyl methacrylate composite nanofibers;

[0045] 5. After spinning, the polyacrylonitrile polymethyl methacrylate composite nanofibers are placed in a muffle furnace, heated to 200°C at a heating rate of 1°C / min and calcined for 2h for material aging treatment, then heated to 500°C at a heating rate of 3°C / min and calcined for 4h, and then heated to 850°C at a heating rate of 3°C / min for carbonization for 12h. After cooling, low voltage drop and high entropy lithium-rich manganese-based porous oxide nanofibers Li{Li 0.2 Mn 0.5 Ni 0.1 Co 0.1 Al 0.06 Cr 0.04}O2.

[0046] The prepared low voltage drop high entropy lithium-rich manganese-based porous nanofibers can be used to prepare positive electrode materials for lithium-ion batteries.

[0047] Example 3

[0048] This embodiment discloses a low voltage drop high entropy lithium-rich manganese-based porous oxide nanofiber, the chemical formula of which is Li{Li 0.2 Mn 0.4 Ni 0.15 Co 0.15 Al 0.05 Cr 0.05}O2.

[0049] The preparation steps and operating parameters of the above-mentioned low voltage drop high entropy lithium-rich manganese-based porous nanofibers are as follows:

[0050] 1. Dissolve polyacrylonitrile and polymethyl methacrylate in dimethylformamide at a mass ratio of 3:1 and a total mass of 5 g to obtain a polymer solution;

[0051] 2. Dissolve Li, Mn, Ni, Co, Al, and Cr in dimethylformamide at a molar ratio of 1.2:0.4:0.15:0.15:0.05:0.05 to obtain a mixed metal salt solution;

[0052] 3. Mix the mixed metal salt solution and the high molecular polymer solution and stir continuously for 2 to 10 hours to obtain an intermediate mixed solution;

[0053] 4. The obtained intermediate mixed solution was transferred into a syringe, and electrospinning was performed by electrospinning at a receiving distance of 12 cm, a flow rate of 1.0 mL / h adjusted by a syringe pump, and a voltage of 18 kV to obtain non-woven polyacrylonitrile polymethyl methacrylate composite nanofibers;

[0054] 5. After spinning, the polyacrylonitrile polymethyl methacrylate composite nanofibers are placed in a muffle furnace, heated to 200°C at a heating rate of 1°C / min and calcined for 2h for material aging treatment, then heated to 500°C at a heating rate of 3°C / min and calcined for 4h, and then heated to 850°C at a heating rate of 3°C / min for carbonization for 12h. After cooling, low voltage drop and high entropy lithium-rich manganese-based porous oxide nanofibers Li{Li 0.2 Mn 0.4 Ni 0.15 Co 0.15 Al 0.05 Cr 0.05}O2.

[0055] The prepared low voltage drop high entropy lithium-rich manganese-based porous nanofibers can be used to prepare positive electrode materials for lithium-ion batteries.

[0056] Experimental example, electrochemical performance test

[0057] Production and electrical performance test of button half-cell:

[0058] Assemble lithium-ion button half-cells (CR2032 type) and detect the electrochemical properties of the materials prepared in each embodiment as positive electrode active materials. Cut the sample into electrode sheets with d = 14 mm and use them directly as electrodes, with lithium sheets as counter electrodes, Celgard 2600 as diaphragms, and electrolytes of 1 mol / L-1 LiPF6 and 0.2 mol / L LiDFOB (solvents are fluoroethylene carbonate FEC / ethyl methyl carbonate EMC / ethyl 2,2-difluoroacetate DFEA = 1:2:1). The battery is assembled in a glove box filled with high-purity argon, with water and oxygen concentrations below 1 ppm. Perform battery charge and discharge tests using the Newway battery test system.

[0059] The low voltage drop high entropy lithium-rich manganese-based porous nanofibers prepared in Example 1 were observed using a scanning electron microscope (SEM). Figure 1 As shown, the diameter of the electrospun fibers is about 400 nm, and the porous nanofibers have good morphology, without obvious adhesion or primary particle growth and annealing, indicating that the spinning conditions are appropriate and doping does not affect the morphology of the nanofibers.

[0060] The low voltage drop high entropy lithium-rich manganese-based porous oxide nanofibers Li{Li 0.2 Mn 0.4 5Ni 0.15 Co 0.1 Al 0.05 TM 0.05}O2 is prepared into a positive electrode sheet and assembled into a battery. The specific preparation method of the positive electrode sheet is: using the prepared high-entropy lithium-rich manganese-based porous oxide nanofibers as the active material, acetylene black is selected as the conductive agent, and polyvinylidene fluoride (PVDF) is selected as the binder. They are weighed in a mortar according to a ratio of 8:1:1, and evenly ground and mixed for 30 minutes, and then a certain amount of N-methylpyrrolidone (NMP) is added, and then evenly ground for 30 minutes to obtain a slurry with a certain viscosity. An automatic coating machine is used to obtain an electrode sheet with uniform thickness, and then it is placed in a vacuum drying oven at 120°C for one night. Then, the dried electrode sheet is rolled with an automatic roller press, and then the electrode sheet is placed on a punching machine and cut into circular electrode sheets of the same size with a diameter of 14 mm to obtain a positive electrode sheet;

[0061] The present invention adopts CR2032 button half-cell, and the whole process is carried out in a glove box (filled with argon gas), and the cycle and rate performance of the battery are tested using a charge and discharge tester. Figure 2 This is a cycle performance diagram of a battery prepared using porous nanofibers of Example 1. It can be clearly seen from the figure that the discharge capacity is 282 mAh / g at 1C, and the discharge capacity is still maintained at 281 mAh / g after 200 cycles, and the cycle retention rate reaches 99.6%. Cyclic voltammetry and electrochemical impedance spectroscopy were performed using an electrochemical workstation, wherein the voltage range of the test was 2 to 4.8 V. Figure 3 The number of cycles reaches 200 in the voltage range of 2.0 to 4.8 V, and the voltage decay is 0.9 mV / cycle.

[0062] The low voltage drop high entropy lithium-rich manganese-based layered oxide porous nanofibers prepared by the present invention have a porous structure. The porous fiber material can improve the electrical conductivity of the high entropy lithium-rich manganese-based positive electrode material particles. At the same time, its large specific surface area significantly improves the first-cycle coulombic efficiency, cycle performance and rate capability of the lithium-rich manganese-based positive electrode material, and inhibits the transformation of the layered structure of the cobalt-free lithium-rich manganese-based positive electrode material to the spinel structure, thereby effectively improving the electrochemical performance of the battery positive electrode material and making a certain contribution to the future development of battery materials.

Claims

1. A high entropy lithium-rich manganese-based porous oxide nanofiber, characterized in that: The chemical formula of the high entropy lithium-rich manganese-based porous oxide nanofiber is Li{Li 0.2 Mn a Ni b Co c Al d TM 0.8-a-b-c-d }O2, wherein 0.4≤a≤0.5, 0.1≤b≤0.2, 0.1≤c≤0.2, 0.01≤d≤0.05; the TM metal element comprises one of Ti, V, Cr, Zr, Mo, W, Nb, Ru, Sn, Ce, and La; The high-entropy lithium-rich manganese-based layered oxide porous nanofibers are prepared by the following steps: S1, dissolving polyacrylonitrile and polymethyl methacrylate in dimethylformamide to obtain a polymer solution; S2, dissolving lithium salt, manganese salt, nickel salt, cobalt salt, aluminum salt, and TM salt in dimethylformamide according to a molar ratio to obtain a mixed metal salt solution; S3, adding the mixed metal salt solution to the polymer solution and mixing evenly to obtain an intermediate mixed solution; S4, transferring the intermediate mixed solution to a syringe, and adopting a high-voltage electrospinning method to obtain a precursor nanofiber; S5, drying the precursor nanofiber and then calcining it in stages, and after cooling, the high-entropy lithium-rich manganese-based layered oxide porous nanofibers are obtained.

2. A method for preparing high entropy lithium-rich manganese-based layered oxide porous nanofibers as claimed in claim 1, characterized in that: The following steps are involved: S1, dissolving polyacrylonitrile and polymethyl methacrylate in dimethylformamide to obtain a high molecular polymer solution; S2, dissolving lithium salt, manganese salt, nickel salt, cobalt salt, aluminum salt and TM salt in dimethylformamide according to a molar ratio to obtain a mixed metal salt solution; S3, adding the mixed metal salt solution to the high molecular polymer solution and mixing evenly to obtain an intermediate mixed solution; S4, transferring the intermediate mixed solution into a syringe, and preparing precursor nanofibers by high-voltage electrospinning; S5, drying the precursor nanofibers and then calcining them in stages, and obtaining the high-entropy lithium-rich manganese-based porous oxide nanofibers after cooling.

3. The method for preparing high entropy lithium-rich manganese-based layered oxide porous nanofibers according to claim 2, characterized in that: In step S2, the lithium salt is a mixture of one or more of lithium carbonate, lithium hydroxide, lithium chloride, and lithium acetate; the manganese salt is a mixture of one or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate; the nickel salt is a mixture of one or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate; the cobalt salt is a mixture of one or more of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate; the aluminum salt is a mixture of one or more of aluminum sulfate, aluminum nitrate, and aluminum chloride; and the TM salt is a mixture of one or more of hydrochloride, sulfate, and nitrate.

4. The method for preparing high entropy lithium-rich manganese-based layered oxide porous nanofibers according to claim 3, characterized in that: In the mixed metal salt solution of step S2, the ratio of the amount of lithium ion, manganese ion, nickel ion, cobalt ion and aluminum ion is 1.2:0.4-0.5:0.1-0.2:0.1-0.2:0.01-0.

05.

5. The method for preparing high entropy lithium-rich manganese-based layered oxide porous nanofibers according to claim 4, characterized in that: During the high-voltage electrospinning process of step S4, the electrospinning voltage is 10-20 kV, the temperature is 25-40° C., the syringe feed rate is 0.001-0.02 mm / s, and the distance between the receiver and the syringe is 15-20 cm.

6. The method for preparing high entropy lithium-rich manganese-based layered oxide porous nanofibers according to claim 5, characterized in that: The step S5 specifically comprises the following steps: S51, heating the dried precursor nanofibers to 200-300° C. at room temperature at a heating rate of 1° C. / min and keeping the temperature for 1.5-2.5 h; S52, heating to 450-550°C at a heating rate of 1.5-4.5°C / min and keeping warm for 3-6h; S53, heating to 800-900°C at a heating rate of 1.5-4.5°C / min and calcining at a constant temperature for 10-18h; after cooling to room temperature, the high-entropy lithium-rich manganese-based layered oxide porous nanofibers are obtained.

7. An application of the high entropy lithium-rich manganese-based layered oxide porous nanofibers as claimed in claim 1, characterized in that: The high-entropy lithium-rich manganese-based porous oxide nanofibers are used to prepare lithium-ion battery positive electrode materials. The lithium-ion battery prepared using the lithium-ion battery positive electrode material has a voltage drop of 0.9 mV / cycle in the first 200 cycles and a 1C capacity of 282 mAh / g.

Citation Information

Patent Citations

  • Lithium ion battery oxide nanotube positive electrode material, preparation method and application

    CN117727906A

  • Voltage-drop-free high-entropy lithium-rich manganese-based layered positive electrode active material as well as preparation and application thereof

    CN117878243A

Cited By

  • Surface-modified high-entropy lithium-manganese-rich positive electrode material as well as preparation method and application thereof

    CN119764379A